Unified dead-time compensation structure for SISO processes with multiple dead times - Normey-Rico, Julio E.; Flesch, Rodolfo C.C.; Santos, Tito L.M. (ISA transactions, 2014)
This paper proposes a dead-time compensation structure for processes with multiple dead times. The controller is based on the filtered Smith predictor (FSP) dead-time compensator structure and it is able to control stable, integrating, and unstable processes with multiple input/output dead times. An equivalent model of the process is first computed in order to define the predictor structure. Using this equivalent model, the primary controller and the predictor filter are tuned to obtain an internally stable closed-loop system which also attempts some closed-loop specifications in terms of set-point tracking, disturbance rejection, and robustness. Some simulation case studies are used to illustrate the good properties of the proposed approach. •The proposed method gives a unified approach for dead-time compensation of processes with multiple time delays.•The structure is simple and easy to tune.•Robustness and closed-loop performance are considered in the design.•The disturbance rejection can be faster than the open-loop dynamics.